Editorial - The Editors (Laureate Education Inc, 2012)
In this second issue of the Higher Learning Research Communications (HLRC) journal we are pleased to continue in our commitment to innovation in teaching and learning. Thought leadership and research of scholars from Spain, Chile, and the United States on such topics as ranking systems, the web and social media to promote powerful learning communal opportunities, action research project on key skill development, and reflections on the value of liberal education contribute to such discourse. Despite the often controversial nature of higher education institutional classifications or rankings, such systems continue to emerge globally.Aguillo examines a multiplicity of ranking systems with a particular focus on Web Ranking with both its concomitant challenges and opportunities in its application. Further demonstrating the power of web and social media as forces for enhancing higher education, Coronel and Mathai describe the global participation of students and faculty in localized and virtual contexts in the World Business Forum produced by HSM Global. Over 50,000 viewers across 19 countries participated in the event which was broadcast in English and Spanish. In accord with the Bologna declaration, academic programme objectives and outcomes need to include professional skills expectations. In the third article in this issue, Fernández-Santander, García-García, Sáez-Pizarro and Terrón-López offer an action research project to determine, develop, and assess key employability skills. The approach provides not only a glossary of competency terms and assessment rubrics; it also serves as a potential model for other institutions to follow that is inclusive of key stakeholder input. Shifting focus from the importance of professional skills, Eastwood offers a cogent argument on the value that components of a liberal or general education bring to how students navigate and understand the world. Consistent with the spirit and intent of HLRC, individually and collectively the work of these authors gives us reason to reflect, to challenge commonly held paradigms, and even to act to create and sustain meaningful learning environments for students.